ANALISIS KADAR HEMOGLOBIN (Hb) DALAM DARAH DAN PENGARUHNYA TERHADAP KELELAHAN KERJA PADA PEKERJA WANITA - Ulfah, Nur; Purnamasari, Dyah Umiyarni (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2012)
ABSTRACT Decline of global economic conditions  are impact on industrial sectors, especially the industries whose products are exported to developed countries and developing countries. These conditions, more employers will do efficiency and focuses  on efforts to overcome the problem of capital management and marketing. Occupatinal health and safety is a part that requires a highcost for the company so it is not important in the current economic. One of negleted component is fatique on the worker. Therefore, researchers wanted to conduct research about the relationship between Hb levels with fatique on the  female workers in PT. HyupSung  Purbalingga. The  results of  bivariate analysis is obtained  p value = 0.075> ? = 0.05. This indicates that there is no significant relationship between Hb levels with fatigue. This is probably caused by Hb workers are still in the normal category, so the possibility of fatigue is caused by other factors. As for suggestions for this research is need for the application of ergonomic principles in working facilities such as tables, chairs,  to reduce helath problems at the waist and back. The need for increased knowledge about the importance of nutrition for the workers.  The need of training fatigue management to problem solving  of fatique on the worker. Keyword :  Hb Levels, Fatique, Worker Kesmasindo Volume 5(1) Januari 2012, hlm. 1-11